Controversial Testimony of Vincas Krėvė-Mickevičius Concerning Lithuania’s Occupation in 1940 to the Kersten Committee of the U. S. Congress after the Second World War - Tamošaitis, Mindaugas (Genocidas ir rezistencija, 2004)
This article presents the testimony of the former Prime Minister and Minister of Foreign Affairs of the People’s Government, Vincas Krėvė-Mickevičius, concerning the tragic events of 1940 in Lithuania, given to the Kersten Committee, which had been created by the U. S. Congress in 1953 to investigate the forced incorporation of Lithuania, Latvia and Estonia into the Soviet Union. Krėvė and other invited important witnesses would first be interrogated by Lithuanian diplomats, and on the next day they would be presented to the American Committee ready for the interrogation. Lithuanian diplomats and the Kersten Committee were surprised by the evidence presented by Krėvė, which clearly differed from the information provided by other witnesses about the same events. It was decided to exclude his testimony from the Committee’s publication, except the part of V. Krėvė’s reminiscences, "Conversation at with Molotov in Moscow". In his testimony Krėvė justified his activities before the occupation in 1940 and failed to disclose his pro-Soviet actions during that period. Although not all the facts could be verified due to inaccessibility of the main documents, Krėvė’s evidence and that of the others were enough to see that he was lying. The Kersten Committee often used the phrase "a la Krėvė", meaning that a witness was talking like Mr. Krėvė, i.e. telling lies. The standing of Krėvė was damaged by his constant pointless polemics with the head of the Lithuanian diplomatic corps, Stasys Lozoraitis, who mentioned to the Congressman Kersten himself that the Lithuanian Association for the Understanding the Culture of the Nations of the USSR was established without his efforts. Lithuanian diplomats did not inform the Lithuanian people about Krėvė’s controversial testimony. Because of this the writer’s political activities and memoirs were considered in a positive light for some decades afterwards.